2014
DOI: 10.1038/leu.2014.4
|View full text |Cite
|
Sign up to set email alerts
|

High number of additional genetic lesions in acute myeloid leukemia with t(8;21)/RUNX1-RUNX1T1: frequency and impact on clinical outcome

Abstract: t(8;21)/RUNX1-RUNX1T1-positive acute myeloid leukemia (AML) is prognostically favorable; however, outcome is heterogeneous. We analyzed 139 patients with t(8;21)/RUNX1-RUNX1T1-positive AML (de novo: n=117; therapy-related: n=22) to determine frequency and prognostic impact of additional genetic abnormalities. All patients were investigated for mutations (mut) in ASXL1, FLT3, KIT, NPM1, MLL, IDH1, IDH2, KRAS, NRAS, CBL and JAK2. Sixty-nine of 139 cases (49.6%) had 1 mutation in addition to RUNX1-RUNX1T1, and 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
105
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(134 citation statements)
references
References 43 publications
22
105
2
5
Order By: Relevance
“…Она встречается приблизительно у 7-8 % взрослых больных ОМЛ и у 12-14 % детей [1][2][3]. Согласно по-следней международной классификации ВОЗ 2008 г., этот вариант ОМЛ относится к категории лейкозов c повто-ряющимися генетическими аномалиями и относительно благоприятным прогнозом.…”
Section: Introductionunclassified
See 3 more Smart Citations
“…Она встречается приблизительно у 7-8 % взрослых больных ОМЛ и у 12-14 % детей [1][2][3]. Согласно по-следней международной классификации ВОЗ 2008 г., этот вариант ОМЛ относится к категории лейкозов c повто-ряющимися генетическими аномалиями и относительно благоприятным прогнозом.…”
Section: Introductionunclassified
“…Поскольку эти больные хорошо отвечают на повторные курсы цитарабина в высоких дозах (HiDAC) [4], они не рассматриваются в качестве кандидатов для аллогенной трансплантации гемопоэтических стволовых клеток (аллоТГСК) в первой ремиссии. Между тем доля рецидивов после стандартной химиотерапии достигает 40-50 % [3,5], а результаты аллоТГСК не столь удовлетворительны [6][7][8][9].…”
Section: Introductionunclassified
See 2 more Smart Citations
“…While study on 93 CN-AML patients demonstrated that RUNX1 found to be 16.1% and it were associated with a lower CR rate and with inferior DFS and OS than wild type patients [124]. Recurrent translocation involving RUNX1 include t(8;21)(q22;q22) RUNX1-RUNX1T1 which is most frequent translocation 15-20% of all AML [125,126]. Somatic mutations clustering within the Runt domain of RUNX1 have been described in MDS and AML [127].…”
Section: Runx1 Mutationsmentioning
confidence: 99%